PERFORMANCE OF DIFFERENT BREEDS OF PIGS IN AN ORGANISED FARM (Indian Journal of Animal Production and Management, 2014)
A study was carried out at 30-sow Teaching Unit, College of Veterinary Science, AAU, Khanapara Campus for a period of ten years to assess the performance of Hampshire (H), Large Black (LB) and Hampshire x Large Black (H x LB) crosses reared under intensive feeding and management. The average litter size and litter weight at birth and at weaning were found to be 8.59±0.28, 7.33±0.32, 8.69±0.42 and 12.33±0.41, 10.02±0.47 and 12.61±0.74 and litter size and litter weight at weaning were 7.44±0.32, 6.40±0.43 and 8.02±0.50 and 101.21±4.30, 81.71±5.48 and 106.80±6.86 respectively in Hampshire, Large Black and crossbred pigs. The litter size at birth and litter weight at birth was significantly higher in Hampshire and crossbred than Large Black pigs. Similarly litter size and litter weight at weaning was also found to be significantly higher in Hampshire and crossbred pigs. Pre-weaning mortality of piglets was recorded 11.30%, 8.68% and 6.04% in Hampshire, Large Black and crossbred piglets respectively. The farrowing number did not have any significant effect on litter size and litter weight at birth and at weaning among the breeds reared upto 5th farrowing. Analysis of data revealed non-significant difference in farrowing intervals due to the effect of parity among the breeds. The analysis revealed better performance of Hampshire and Crossbred pigs in comparison to Large Black pigs.
Keywords: Hampshire; Large Black; litter size; farrowing interval; parity